Dupilumab for Systemic Allergy Syndrome With Dermatitis. Issue 2 (March 2019) - Jacob, Sharon E.; Sung, Calvin T.; Machler, Brian C.
Abstract : Allergic contact dermatitis (ACD) has been traditionally identified as TH 1-mediated delayed-type hypersensitivity reactions. There is currently no Food and Drug Administration–approved systemic therapy indicated for ACD. Among patients with ACD, there is a subgroup that experience not only concomitant atopic dermatitis and ACD but also systemic allergic dermatitis driven by allergens encountered through dietary consumption. Basic science and clinical studies have supported the notion that ACD involves a complex interaction between both TH 1 and TH 2 axes of the secondary immune system on an allergen-by-allergen basis. Herein, we report the patients with systemic allergy syndrome with dermatitis to either Balsam of Peru or nickel who achieved remarkable improvement and regained their quality of life without continuing adherence to strict diets. Our study suggests that dupilumab may be an efficacious solution for a particular subgroup of patients with recalcitrant ACD when first- and second-line therapies have failed.